MISSENSE MUTATIONS IN THE IRAK1 GENE ARE ASSOCIATED WITH AN INCREASED RISK OF SYSTEMIC LUPUS ERYTHEMATOSUS - Adnan Adnan; Dyah Aryani Perwitasari; Rita Maliza; Nanik Sulistyani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Single nucleotide polymorphisms (SNPs) are the most common form of genetic variation in humans. Missense SNPs can change protein structure and function. This study aimed to determine missense SNPs of the IRAK1 gene that can affect the amino acid sequence and lead to changes in protein structure and function, as well as their relationship as a risk factor for SLE. In this in silico method, several bioinformatics tools have been used to identify missense SNPs, including their properties and impacts, as well as their interaction networks with proteins. The tools used were PolyPhenv2, SIFT, PhD-SNP, PROVEAN, SNAP, Panthers, I-Mutant 3.0, and GeneMania. Four missense SNPs, rs11465830, rs1059702, rs1059703, and 10127175, were obtained from the NCBI SNP database. The SIFT test results showed that all the SNPs were tolerant. In the test results obtained using PolyPhen, the four SNPs were benign. The results of the probe test indicated that the four SNPs were neutral. When tested with SNAP, one SNP was neutral, and three others had an impact. In the PhD-SNP test, all SNPs were neutral. In the panther test, all SNPs were benign. The I-mutant assay showed that the four SNPs could decrease protein stability. Tests with GeneMania have reported that most interactions between genes were between IRAK1 and MYD88, and physical interactions were the most dominant form of interaction. Conclusion. rs10127175, rs11465830, rs1059702, and rs1059703 are missense SNPs in IRAK1, which can disrupt protein stability and be a risk factor for SLE. Keywords: IRAK1, SNP, Missense, Systemic Lupus Erythematosus